2016
DOI: 10.1038/srep37106
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting trap states in planar PbS colloidal quantum dot solar cells

Abstract: The recently developed planar architecture (ITO/ZnO/PbS-TBAI/PbS-EDT/Au) has greatly improved the power conversion efficiency of colloidal quantum dot photovoltaics (QDPVs). However, the performance is still far below the theoretical expectations and trap states in the PbS-TBAI film are believed to be the major origin, characterization and understanding of the traps are highly demanded to develop strategies for continued performance improvement. Here employing impedance spectroscopy we detect trap states in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 45 publications
(62 reference statements)
6
64
0
3
Order By: Relevance
“…In order to understand the increase of V oc , capacitance–voltage (C −2 –V) measurements were performed to further investigate the change of the built‐in electric field of the CsPbI 2 Br PSCs with the Eu(Ac) 3 dopant. Figure S5, Supporting Information, shows the C −2 –V plots for the CsPbI 2 Br PSCs, from which the built‐in potential was obtained based on the Mott–Schottky equation of C −2 = (2( V bi − V ))/( A 2 eεε 0 N A ), where C is the capacitance under applied voltage ( V ), V bi is the built‐in potential, V is the applied voltage, A is the device area, ε is the relative permittivity, ε 0 is the vacuum permittivity, and N A is the carrier concentration . The V bi for the PSC made with 0.5 mol% Eu(Ac) 3 dopant is 1.02 V, which is larger than 0.95 V as obtained for the control device.…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the increase of V oc , capacitance–voltage (C −2 –V) measurements were performed to further investigate the change of the built‐in electric field of the CsPbI 2 Br PSCs with the Eu(Ac) 3 dopant. Figure S5, Supporting Information, shows the C −2 –V plots for the CsPbI 2 Br PSCs, from which the built‐in potential was obtained based on the Mott–Schottky equation of C −2 = (2( V bi − V ))/( A 2 eεε 0 N A ), where C is the capacitance under applied voltage ( V ), V bi is the built‐in potential, V is the applied voltage, A is the device area, ε is the relative permittivity, ε 0 is the vacuum permittivity, and N A is the carrier concentration . The V bi for the PSC made with 0.5 mol% Eu(Ac) 3 dopant is 1.02 V, which is larger than 0.95 V as obtained for the control device.…”
Section: Resultsmentioning
confidence: 99%
“…[13,14] For PbS treated with tetrabutylammonium iodide (TBAI) a trap distribution with an activation energy of 0.34 eV was found via temperature-dependent impedance spectroscopy. [15] Using optical pump-probe spectroscopy, the groups of Asbury and Sargent observed a broad photoinduced absorption (PIA) around 0.3 eV with a long lifetime (still visible after 200 µs) for a range of ligands, including EDT and MPA, and attributed this observation to surface trap states. [16,17] Bakulin et al finally reported two distributions, independent of each other, at activation energies of 0.2 and 0.3-0.5 eV for EDT and MPA capped PbS, distinguishable by their lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Tatsächlich wurden allein im Jahr 2017 weltweit über 100 GW Solarmodule installiert, wobei der Markt immer noch von kristallinen Silicium-Modulen, den Solarzellen der ersten Generation, beherrscht wird. [3] Sie machten 2017 rund 5%der insgesamt hergestellten Module aus.Z ud en Zellen dritter Generation gehçren eine Reihe von Dünnschichtzellen, darunter farbstoffsensibilisierte, [4] Polymer-, [5] Quantenpunkt- [6,7] und Halogenidperowskit(HaP)-Zellen. Hinzu kommen anwendungsabhängige Nachteile wie die relativ schlechte Leistung bei hohen Te mperaturen und unter schwachen Lichtverhältnissen sowie ihre starre und relativ schwer Bauart.…”
Section: Einführungunclassified
“…So ist beispielsweise die bei RT stabile Phase von CsPbI 3 die gelbe d-Phase,d ie als Photovoltaik-Material relativ inaktiv ist, während die sogenannte schwarze Phase (a-Phase) bei RT nur unter besonderen Bedingungen stabil ist. [25] Senkt man die Temperatur von dem Bereich ab,i nd em die kubische "Hochtemperatur"-Phase stabil ist, verformen sich die PbX 6 der kubischen in die geringer symmetrische tetragonale Form und schließlich in die orthorhombische Form um. [24] Andererseits ist die stabile Form von CsPbBr 3 bei RT die orthorhombische g-Form.…”
Section: Kristallstrukturunclassified